(3JMdjd GdeJZjQGJ GdGbJUGOjIs - (3fHjd GHQGgje eMehO(B, (3GdWGFjs ((3YeGf(B:s (3OGQ GdHOGjI(B,s, 2008)
(3GdEfJGLjI hGdcaGAI (BProductivity & Efficiency : (3GdEfJGLjI (BProductivity : (3eaghe GdEfJGLjI (B: (3GdeaGgje GdLRFjI ddEfJGLjI (B: (3GdeaGgje GdcdjI ddEfJGLjI (B: (3JYQja GdEfJGLjI (B: (3eRGjG hahGFO ebGjjS GdEfJGLjI (B: (3eTGcd bjGS GdEfJGLjI (B: (3eDTQGJ GdEfJGLjI Ydi eSJhi GdbWGY GdUfGYj (B: : (3bjGS GdEfJGLjI HGSJNOGe GdCQbGe GdbjGSjI (B: (3GdcaGAI (BEfficiency : (3JYQja GdcaGAI (B: (3CfhGY GdcaGAI(B-(3GdaUd GdKGfj (B: (3GdJZjQ GdJbfj (BTechnical Change : (3eaghe GdJZjQ GdJbfj (B: (3ehbY eJZjQ GdJZjQ GdJbfj aj GdfXQjI GdGbJUGOjI (B: (3JWhQ GdeYGdLI GdQjGVjI ddJZjQ GdJbfjj(B-(3GdaUd GdKGdK (B: (3GdYed hQCS GdeGd (BLobour & Capital : (3GdYed (B: (3QCS GdeGd (B: (3WQb bjGS GdeNQLGJ hGdeONdGJ(B.s
Keywords: (3GbJUGOs; (3eJZjQGJ GbJUGOjIs